ANALYSIS OF SOME BIOLOGICAL PROPERTIES OF SOYBEAN PLANT (Conferencea, 2023)
Nowadays, it is not a secret to anyone that soybean (Glycine hispida maxim) has been added to the list of plants that have high nutritional value, such as lentils, beans, peas, sorghum, wheat, barley, oats, and corn [1 -2]. Globally, today's gross production of the soy plant, which is rich in macro and microelements, equal to the above-mentioned plants, is 276,500 million tons. The cultivated area of this gross product on the world market is 111,300 thousand hectares across the globe. If we talk about productivity, it corresponds to 24.8 ts/ha [3-5].